Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.2991/jnmp.1994.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Antireduction and exact solutions of nonlinear heat equations

Abstract: We construct a number of ansatzes that reduce one-dimensional nonlinear heat equations to systems of ordinary differential equations. Integrating these, we obtain new exact solution of nonlinear heat equations with various nonlinearities.3/2 1 ϕ 3 + ϕ 4 , ϕ i = ϕ i (x 0 , x 2 ).(4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 2 publications
0
60
0
Order By: Relevance
“…Examples from the previous works are used. It is concluded that Adomian Decomposition Method provides both exact and approximate numerical solutions for the heat equations with nonlinear power in comparison to other solutions such as antireductiori method (Fushchych& Zhdanov, 1994) and Lie symmetry reduction method (Euler & Euler, 1997 …”
Section: Discussionmentioning
confidence: 99%
“…Examples from the previous works are used. It is concluded that Adomian Decomposition Method provides both exact and approximate numerical solutions for the heat equations with nonlinear power in comparison to other solutions such as antireductiori method (Fushchych& Zhdanov, 1994) and Lie symmetry reduction method (Euler & Euler, 1997 …”
Section: Discussionmentioning
confidence: 99%
“…We also have g 2 ∩ g 2 ∼ su(2) ⊕ su(2) ∼ so (4), from which we conclude that G 2 has no realizations by operators of the form (8) which are symmetry operators of (1).…”
Section: Theoremmentioning
confidence: 95%
“…if we take into account that the algebras so (3,2) and so(4, 1) contain so (3,1), and the algebra so(5) contains so (4).…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical method for finding symmetry reductions of PDEs is the Lie group method of infinitesimal transformations [13][14][15]. Several generalizations to the classical method have been introduced, these include the nonclassical method [16], the direct method [17][18][19][20] and the generalized conditional symmetry method [21][22][23][24][25]. The symmetry related methods have been successfully applied to seek exact solutions and symmetry reductions of nonlinear PDEs.…”
Section: Introductionmentioning
confidence: 99%